Identification and Apportionment of Sources of Ozone-forming Potential for Proper Reduction Strategies - Demir, Selami; Saral, Arslan (WILEY-BLACKWELL, 2013)
In this study, results of source identification and apportionment for ambient volatile organic compounds (VOCs) from a previous work were used to estimate ozone-forming potentials (OFPs) of effective sources for developing proper strategies for reduction of tropospheric ozone pollution. The source identification and apportionment of ambient VOC pollution within Yildiz Technical University's Davutpasa Campus (Istanbul, Turkey) was done by positive matrix factorization (PMF). The results suggested five effective source groups with the emissions related with paint use and solvent use having the highest contributions (36.8 and 28.2%). The results from PMF were used along with maximum incremental reactivities to estimate potentials of individual sources for ozone formation. It was found that biogenic emissions (3.78) and traffic related emissions (gasoline and diesel vehicle exhaust) (3.83 and 3.15, respectively) have the highest potential for ozone formation in terms of grams O3/g VOC emitted. The results were used to suggest proper source-based reduction strategies for OFP.
Keywords: Ozone precursor; Photochemical reaction; Tropospheric ozone; VOCs; VOLATILE ORGANIC-COMPOUNDS; POSITIVE MATRIX FACTORIZATION; LIQUEFIED PETROLEUM GAS; CHEMICAL MASS-BALANCE; COMPOUNDS VOCS; DIURNAL-VARIATIONS; RECEPTOR MODELS; AIR; ATMOSPHERE; EMISSIONS; Science & Technology - Other Topics; Environmental Sciences & Ecology; Marine & Freshwater Biology; Water Resources